On-sun demonstration of a 750 °C heat transfer fluid for concentrating solar systems: Dense particle suspension in tube. (August 2015) - Benoit, H.; Pérez López, I.; Gauthier, D.; Sans, J.-L.; Flamant, G.
Graphical abstract: Highlights: A one-tube solar receiver containing upward particle suspension was operated on-sun. Outlet powder temperatures up to 750 °C were obtained experimentally. Absorber wall temperatures were measured accurately. Temperature measurements reveal a powder reflux mode inside the vertical tube. Wall-to-suspension heat transfer coefficients were found in the range 420–1100 W/m 2  K. Abstract: A dense particles suspension was tested in a high temperature single tube on-sun solar receiver at the French National Centre for Scientific Research (in French: Centre National de la Recherche Scientifique = CNRS) solar facility. A powder outlet temperature as high as 750 °C was measured thus proving the capacity of this heat transfer fluid concept to reach high operating temperatures. The wall-to-suspension heat transfer coefficient was calculated on the basis of detailed temperature measurements and accounting for the strong recirculation phenomena occurring at the tube wall. It ranges from 420 W/m 2  K to 1100 W/m 2  K for a solid mass flux of 10 kg/m 2  s and 45 kg/m 2  s, respectively. The temperature increase positively influences the heat transfer coefficient; with a 30% increase measured between ∼200 °C and 600 °C average powder temperatures. Finally, a correlation is proposed to predict the dependency of the heat transfer coefficient and solid mass flux.